Geotectonic and geothermal conditions of the gas discharge zones in the Black Sea - R.I. Kutas (Геофизический журнал, 2020)
This paper presents the investigation results of geodynamic, geothermal and geochemical conditions of gas emission zones in the anoxic Black Sea Basin. Gases are manifested in the form of seeps, fountains, mud volcanoes (MV), gas hydrates and authigenic carbonates. Several thousand gas seeps and more than 80 MVs have been found in the Black Sea Basin. Most of them are associated with fault zones, abyssal fractures, shale diapir and others zones of neo-tectonic activity. Gas seeps occur mostly on the outer shelf and in the upper part of continental slope (at a depth of 50—800 m), and MVs are distinguished in the central and the most submerged part of the Western Black Sea sub-basin, as well as in the periphery troughs. Gas hydrates occur in subsurface sedimentary layers near MVs and gas seeps at a water depth of more than 700 m. Methane is the dominant component among natural gases (90—95 %) from seeps and MVs. Methane homologous, carbon dioxide, hydrogen sulphide, nitrogen etc. are also present in different proportions. Breccia from MVs also contains oil components, different minerals (carbonates, sulphides, sulphates, phosphates) and dispersed particles of native metals. Based on seismic refraction data, the feeder channels of MVs penetrate to the base of Maykop sediments or to the Mesozoic basement (at a depth of 10—16 km). An analysis of the isotopic composition of methane from different sources (sediments, seeps, MVs and authigenic carbonates) has been performed. The stable carbon isotopic composition values (13C) range from -90 ‰ to -30 ‰ in methane and from -46.9 ‰ to - 8.5 ‰ in carbonates. Carbon isotopic composition in methane depends on its origin (organic or anorganic), as well as on thermodynamic conditions of its formation and migration. Changes in these conditions are accompanied by changes in chemical composition of hydrocarbon gases (from СО2 to СН4), as well as by isotopic composition fractionation of their components. These changes are possible only under mantle conditions. Heterogeneity of carbon isotopic composition in methane of the Black Sea Basin represents the variety of terms of its formation and is coherent with geotectonic zoning at the level of basement, as well as with peculiarities of geodynamic and geothermal conditions. Such coherence attests a significant (maybe even critical) role of abyssal processes in Earth degassing.